Petrogenesis and U-Pb and Sm-Nd geochronology of the Taquaral granite: record of an orosirian continental magmatic arc in the region of Corumba - MS - REDES, Letícia Alexandre (Universidade Federal do Pará, 2017)
The Taquaral Granite is located on southern Amazon Craton in the region of Corumbá, westernmost part of the Brazilian state of Mato Grosso do Sul (MS), near Brazil-Bolivia frontier. This intrusion of batholitic dimensions is partially covered by sedimentary rocks of the Urucum, Tamengo Bocaina and Pantanal formations and Alluvial Deposits. The rock types are classified as quartz-monzodiorites, granodiorites, quartz-monzonites, monzo and syenogranites. There are two groups of enclaves genetically and compositionally different: one corresponds to mafic xenoliths and the second is identified as felsic microgranular enclave. Two deformation phases are observed: one ductile (F1) and the other brittle (F2). Geochemical data indicate intermediate to acidic composition for these rocks and a medium to high-K, metaluminous to peraluminous calk-alkaline magmatism, suggesting also their emplacement into magmatic arc settings. SHRIMP zircon U-Pb geochronological data of these granites reveals a crystallization age of 1861 ± 5.3 Ma. Whole rock Sm-Nd analyses provided εNd(1,86 Ga) values of -1.48 and -1.28 and TDM model ages of 2.32 and 2.25 Ga, likely indicating a Ryacian crustal source. Here we conclude that Taquaral Granite represents a magmatic episode generated at the end of the Orosirian, as a part of the Amoguija Magmatic Arc.